Disability and its relationship to sociodemographic and clinical variables in adults of San Juan de Pasto, Nariño in Colombia - Gil Obando, Lida Martiza; López López, Alexandra; Avila Rendón, Carmen Liliana; Criollo Castro, Carlos Hernando; Canchala Obando, Alexandra Marcela; Serrato Medoza, Maria Paula (Universidad y Salud, 2016)
Introduction: Disability evaluation involves analysis from a corporal, social and personal level. Objective: To correlate disability with sociodemographic and clinical variables of adults in San Juan de Pasto, Colombia. Materials and Method: A correlational study was made, whose sample consisted of 117 people with disabilities, who were older than 20 years old with more than six months with the disability. WHODAS II was used. Results: The sociodemographic variables: age, age ranges, marital status and occupation presented a significant association with mobility and final disability. The clinical variables: medical diagnosis, time and time ranges of disability, type of external help, use and type of drugs, showed a significant association with the areas of mobility, self-care, relationships with others, daily life activities and participation in society. Conclusions. People with disabilities in this study were mostly men, single and credited a degree of mild disability. Occupation and clinical variables showed greater impact on daily life activities, mobility and global disability.